Sensitivity tests of dimethomorph, ethaboxam and etridiazole on Phytophthora palmivora causing stem rot and leaf blight of durian in eastern Thailand - Veeranee Tongsri; Patcharin Nianwichai; Kamonwan Sichai; Pattavipha Songkumarn; Suttiviriya Pavinee; Pornprapa Kongtragoul; C Agarwal; W Chen; C Coyne; G Vandemark; B Bailey; H Bae; et al. (Agriculture and Natural Resources, 2023)
Importance of the work: Phytophthora palmivora is a major pathogen on durians and has been found to be resistant to metalaxyl.Objectives: To investigate the sensitivity of P. palmivora to alternative fungicides and evaluate its fungicide efficacy for controlling durian diseases. Materials & Methods:The isolates of P. palmivora were evaluated for their fungicide sensitivity to dimethomorph, ethaboxam and etridiazole on the culture medium against mycelial growth, sporangium production and germination.The representative isolates were determined for fungicide sensitivity on durian leaf tissue.The fungicides with low values for the concentration that inhibited the mycelial growth of the isolate by 50% (EC 50 ) were used for durian disease control.Results: The mycelial growth of all P. palmivora isolates was sensitive to dimethomorph, ethaboxam and etridiazole, with mean (± SD) EC 50 values of 0.233 ± 0.116 parts per million (ppm), 0.007 ± 0.002 ppm and 2.945 ± 1.464 ppm, respectively.Sporangium production and germination were also sensitive to all fungicides.The mean EC 50 values on durian leaf tissue were 0.696 ppm for dimethomorph, 0.089 ppm for ethaboxam and 0.766 ppm for etridiazole.Dimethomorph (100 ppm) and ethaboxam (50 ppm) completely reduced disease development on detached leaves; however, etridiazole (50 ppm) showed maximum control of the disease (55.6%).Only ethaboxam (208 ppm) extremely suppressed the disease in a seedling experiment (92.3%), while dimethomorph (500 ppm) produced much less disease control (27%).Etridiazole (240 ppm) could not control the disease in seedling conditions.Main finding: Ethaboxam had the potential to control durian disease caused by P. palmivora in the eastern growing areas of Thailand.Repeat fungicide application should be discussed regarding dimethomorph and etridiazole.
Keywords: Plant Pathogens and Resistance